Ensemble Riemannian data assimilation over the Wasserstein space - S. K. Tamang; S. K. Tamang; A. Ebtehaj; A. Ebtehaj; P. J. van Leeuwen; D. Zou; G. Lerman (Nonlinear Processes in Geophysics, 2021)
In this paper, we present an ensemble data assimilation paradigm over a Riemannian manifold equipped with the Wasserstein metric. Unlike the Euclidean distance used in classic data assimilation methodologies, the Wasserstein metric can capture the translation and difference between the shapes of square-integrable probability distributions of the background state and observations. This enables us to formally penalize geophysical biases in state space with non-Gaussian distributions. The new approach is applied to dissipative and chaotic evolutionary dynamics, and its potential advantages and limitations are highlighted compared to the classic ensemble data assimilation approaches under systematic errors.